Oral Dispersible Tablet: A Popular Growing Technology - Vora, Harsh; Modi, Darshan; Pandya, Vikram; Bharadia, Praful; Patel, Maulik (Asian Journal of Pharmaceutical Research and Development, 2013)
Oral Dispersible tablets are well recognised dosage forms presented in the market. Since their introduction to the market in the 1980s, ODTs have become one of the fastest growing segments of the oral drug delivery industry, and their product pipeline is rapidly expanding. An orally disintegrating tablet or orodispersible tablet (ODT) is a drug dosage form available for a limited amount of over-the-counter (OTC) and prescription medications. ODTs is one such novel approach to increase consumer acceptance by virtue of self-administration without water or chewing which disintegrate or dissolve rapidly in the mouth (saliva) within few seconds.The various advantages that they offer to the patients in terms of massive revenues by line extension of products include a variety of advantages. The development of oral dispersible tablets has been formulated for paediatric, geriatric, and bed rest patients and for those people as well as patients who may not have access to water with improved therapeutic efficacy and patient compliance. Several formulations provide an opportunity for product line extension especially for elderly persons will have difficulties in taking conventional oral dosage forms because of hand tremors and dysphasia and swallowing problem in young individuals due to under developed muscular and nervous systems. This article gives a brief review on the ideal properties, significance, characteristics, limitation, choice of drug candidates, challenges in formulation, the fabrication of Oro-dispersible tablets with a detailed concept of fabricating technologies, patented technologies as well as emerging trends or technologies and Evaluation tests of ODTs.